CaCu3Ti4O12 ceramics with giant permittivity prepared by reduction-reoxidation method. Issue 12 (15th June 2023) - Zu, Hao; Wang, Chuanfeng; He, Xiaojuan; Wang, Bingzheng; Liu, Hui; Huang, Hui; Bian, Jian; Cao, Guohua
Abstract: CaCu3 Ti4 O12 (CCTO) materials are greatly desired in the miniaturized multilayer devices due to the giant permittivity. However, Ni electrode presently cannot be employed as internal electrode for CCTO-based multilayer devices, which is much cheaper than Ag/Pd electrode. This is because Ni electrode should be sintered in protecting atmosphere, which easily led to decomposition of CCTO materials. The decomposition reaction was mainly attributed to the serious Cu-loss during reduction sintering. The Cu-loss can be effectively weakened, when the ceramics were sintered in a close alumina crucible at a relatively low temperature induced by liquid phase. The decomposition reaction was found to be suppressed and dense ceramics were successfully prepared by reduction sintering. Giant permittivity was observed in the reduced CCTO-BN (4.2 × 10 4 ), but dielectric loss (8.88) and nonlinear characteristic deteriorated. This is because the grain boundary could not be oxidized during reduction sintering. The reduced CCTO-BN was then reoxidized in air to promote the oxidation of grain boundary. The dielectric loss was decreased more than 10 2 times to 0.07 and the nonlinear characteristic was reestablished for the reoxidized CCTO-BN. Meanwhile, the relative permittivity still remained a giant value of 1.2 × 10 4 . The findings shed a new light on developing CCTO-based devices with Ni electrode, which helps to significantly reduce the production cost.